Comparative analysis of “Dolls retail“by Sadeq Chubak and “A Corpse on the Pavement’’ by Saadallah Wannous - Saleh Bek Majid; Fatemeh Bayatfar (Matn/Pizhūhī-i Adabī, 2015)
Among Sadegh Chubak's works (Iranian writer) and Saadollah Vannous' works (Syrian play writer), there are many similarities between “dolls retail’’ and “A Corpse on the Pavement’’. In this article, at first the subject and theme of two mentioned works is clearly defined and then structural elementsof these two works are analyzed comparativelyaccordingtoAmerican school. For this purpose, we studied the narrative structure of two mentioned works based on theories of great narratologists such as “William Lebow’’, “Greimas’’ and “Gérard Genette’’ in four sections of character, plot, and time and place perspective. Also, during thereflection onformal and semantic cohesion factors of these two works, we have reviewed and analysed differencesandsimilaritiesbetween them in terms of subject, space, time, place, plot and etc. Finally, besides conclusion, we have talked about the causes of being these two effects among naturalistic worksasthe dominant discourseoncommunities.